Comparative study of anti-angiogenic activities of luteolin, lectin and lupeol biomolecules. - Ambasta, Rashmi K.; Jha, Saurabh Kumar.; Kumar, Dhiraj.; Sharma, Renu.; Jha, Niraj Kumar.; Kumar, Pravir. (2016)
Background: Angiogenesis is a hallmark feature in the initiation, progression and growth of tumour. There are various factors for promotion of angiogenesis on one hand and on the other hand, biomolecules have been reported to inhibit cancer through anti-angiogenesis mechanism. Biomolecules, for instance, luteolin, lectin and lupeol are known to suppress cancer. This study aims to compare and evaluate the biomolecule(s) like luteolin, lupeol and lectin on CAM assay and HT-29 cell culture to understand the efficacy of these drugs.; Keywords: CAM assay, Flavonoids, HT-29 cell, Anti-angiogenesis, Luteolin, Lupeol, Lectin.; Springer Open.